Economic report of the president transmitted to the congress February 1985: together with the annual report of the Council of Economic Advisers - United States President; Council of Economic Advisers (US) (Washington: United State Government Printing Office, 1985)
The book comprises of the 1985 economic report of the president of the United States of America, Ronald Reagan and the Annual Report submitted by the Council of Economic Advisers in accordance with the provisions of the employment Act of 1946 as amended by the full employment and balanced growth Act of 1978.
rpm 07/06/2017
Loans
Keywords: United States -- Economic policy; Economic policy; United States